Surgical Outcomes of Patients with Mental Illness: A Narrative Literature Review - Muhammad Rizqi Firyal (HM Publisher, 2021)
Patients with mental illness face numerous limitations when facing surgical treatment. Some of the most significant limitations include difficulty managing their mental health conditions, increased risk of complications, limited access to health facilities, anxiety and limited communication. This literature review aimed to describe the various challenges that patients with mental illness face when undergoing surgery, the impact of mental illness on surgical outcomes, and strategies to improve outcomes for this patient population. Healthcare providers can also improve outcomes by addressing the unique needs of patients with mental illness during the surgical process. This may include developing specialized protocols for anesthesia and pain management, providing additional support and monitoring during and after surgery, and ensuring that patients receive appropriate follow-up care. In conclusion, surgical outcome in patients with mental illness is a complex and challenging issue. Patients with mental illness face numerous challenges during and after surgery, including limited access to appropriate care, increased risk of complications, and difficulty managing their mental health conditions.